SAT0249 Safety, pharmacokinetics, pharmacodynamics and inhibition of T-cell dependent antibody response (TDAR) with MEDI4920, a novel, engineered CD40 ligand (CD40L) antagonist: results of a first-time-in-human study. (15th June 2017) - Albulescu, MG; Gunsior, M; Li, J; Bush, J; Godwood, A; Miday, R; Grant, E; Howe, D; Faggioni, R; Roskos, L
Abstract : Background: The CD40/CD40L pathway is involved in the T-cell-dependent activation of B cells, which subsequently produce autoantibodies and inflammatory mediators that contribute to autoimmune disease pathology. MEDI4920 is an engineered fusion protein and antagonist of CD40L that lacks the fragment crystallisable (Fc) domain thought to be involved in thromboembolic events (TEs) previously reported with anti-CD40L agents containing an Fc domain. Objectives: The primary objective of this Phase I, randomised, double-blind, placebo-controlled, single-ascending dose study was to evaluate the safety and tolerability of MEDI4920 in healthy subjects. Secondary objectives were to characterize T-cell-dependent antibody response (TDAR) to keyhole limpet hemocyanin (KLH) neoantigen, pharmacokinetics (PK), and anti-drug antibodies (ADAs) to MEDI4920. Methods: Fifty-six healthy adult male subjects, aged 19–49 years, received a single intravenous dose of either MEDI4920 (3, 10, 30, 100, 300, 1000 or 3000 mg) or placebo. TDAR inhibition was analysed by measuring serum concentrations of IgG and IgM antibodies to KLH over time. A dose−response model was generated for TDAR inhibition. Blood samples were collected to evaluate PK, total soluble CD40L (sCD40L) and ADA concentrations. Results: No deaths, TEs, severe or serious hypersensitivity reactions or infections or infusion-related reactions were observed in the study. One serious adverse event (fractured tibia) was reported in the placebo arm. MEDI4920 showed inhibition of the TDAR IgG response after the second administration of KLH on Day 15 at higher doses (≥300 mg; Figure 1 A). An Emax model adequately characterised the TDAR dose−response at Day 43 (p<0.001; ED50 =491 mg), with the 3000 mg dose showing 86% inhibition of the TDAR (95% CI: 68–94%; Figure 1 B). MEDI4920 exhibited linear PK. MEDI4920 produced a dose-dependent increase in total sCD40L concentrations. A high ADA incidence (90%) was observed in dose cohorts ≤100 mg; however, ADA incidence (29%) and ADA titres decreased with ≥300 mg doses of MEDI4920. ADA-high subjects had reduced MEDI4920 and total sCD40L concentrations compared with ADA-negative subjects or those with low ADA titres. ADA incidence did not correlate with any clinical events. Conclusions: MEDI4920 demonstrated an acceptable safety and tolerability profile, and dose-dependent inhibition of TDAR. The dose-dependent increase in total sCD40L concentrations indicates binding of MEDI4920 to sCD40L and target engagement. The decreases in ADA incidence and ADA titres correlate with increasing MEDI4920 dose, consistent with the immunosuppressive mechanism of action of this molecule. These results support further exploration of MEDI4920 administration in subjects with autoimmune diseases where the CD40/CD40L pathway is activated. Acknowledgements: Funded by MedImmune. Medical writing support: D. Trivedi, MedImmune LLC, Gaithersburg, MD, USA. Technical editing support: R. Plant, QXV Comms, an Ashfield company, which was funded by MedImmune. Disclosure of Interest: M. Albulescu Shareholder of: MedImmune, Employee of: MedImmune, M. Gunsior Employee of: MedImmune, J. Li Employee of: MedImmune, J. Bush Employee of: Covance Clinical Research Unit Ltd (Co. contracted [and paid] by the sponsor to conduct the study), A. Godwood Shareholder of: AstraZeneca, Employee of: MedImmune, R. Miday Employee of: MedImmune, E. Grant Shareholder of: AstraZeneca, Employee of: MedImmune, D. Howe Employee of: MedImmune, R. Faggioni Shareholder of: AstraZeneca, Employee of: MedImmune, L. Roskos Shareholder of: AstraZeneca, Employee of: AstraZeneca